(untitled) (Anclajes, 2022)
The article explores the poetics of clipping in a set of texts published in the "Museo" section y Jorge Luis Borges and Adolfo Bioy Casares, in Destiempo (1936-1937) and Los Anales de Buenos Aires (1946-1948) y Jorge Luis Borges and Adolfo Bioy Casares. The manipulation of texts can be linked to modern clipping technology, which responded to the need for brevity, a requirement of the press, as well as literary and editorial procedures implemented in the recovery of texts from the most diverse supports and that enable to think about cutting as rewriting and reinterpretation (Thérenty, 2012; Viu, 2019). Under the name of “Museo”, the published texts are inserted in the semantic field of exhibition and conservation. Regarding the first, it will be analyzed the visuality of the texts. Regarding the second, the strategies of its collection will be studied (Guelfi Campos, 2019). Finally, we will study the new writing modalities that generate fragmentation and synthesis. We hypothesize that these cut poetics diluted the role of the writer as the sole author and implied an intervention on genres.